Neovascular Glaucoma as a Predictor of Retinoblastoma High-Risk Histopathology in an International Multicentre Study - Negretti, GS (2024)
Purpose: To assess histopathology and outcomes following primary enucleation of eyes with retinoblastoma presenting with neovascular glaucoma (NVG). Methods: This was an international multi-centre case series study across five continents. Retrospective review of patient charts was performed for all patients undergoing primary enucleation for retinoblastoma (n=1420) using a standardised data-collection spreadsheet. Clinical features, pathological grade, and outcomes were compared between NVG patients and those with an American Joint Commission on Cancer (AJCC) 8th edition clinical stage of cT2. High-risk histopathology was defined as AJCC 8th edition pathological stage ≥pT2b. Results: NVG was seen in 224/1420 (16%) patients. Mean age at presentation of those with NVG was 30 months (median 25, range 0-120 months) and 131(58%) patients had high-risk histopathology. The univariate logistic regression odds ratio for NVG predicting high-risk histopathology was 1.73 (95% confidence interval: 1.3 to 2.31) and from multivariate logistic regression was 1.77 (95% confidence interval: 1.23 to 2.56). Patients with a longer duration of symptoms (p=0.03), buphthalmos (p=0.02) and ectropion uveae (p<0.01) were more likely to have high-risk histopathology. Patients with NVG were more likely to develop metastasis than cT2 patients (p=0.04). Conclusions: There is a significant association between NVG at presentation, high-risk histopathology and metastatic risk.